Review Legal to Agreement Borrow Borrowing Money Declared Void by Law (Case Study of Decision) Number 451/ Rev.G /2012/ Pn.Jkt.Bar) - Tomy Yosua Harianja; Tri Reni Novita (Fox Justi : Jurnal Ilmu Hukum, 2025)
Where in this case the plaintiff has been legally proven to have defaulted by not fulfilling his obligations in paying debt installments that began on November 30, 2011 until the sending of warning letters. In this case the Plaintiff did not make achievements as agreed by both parties. So that the Defendant suffered a loss caused by the Plaintiff because he was late paying his penalty. Literature review In this thesis, among others, the basic concepts of the agreement and the elements of the agreement, the legitimate terms of the agreement, the principles of the agreement, the borrowing agreement to borrow money, the null and void agreement, the General Review , and the Fiduciary Understanding. This article uses a normative juridical research method or library research and is prescriptive that focuses on formulating recommendations about the steps that must be taken in solving certain problems. The results of this study are PT Bangun Karya Lestari fulfilling the elements of default, namely the existence of an agreement, a loss, an error, and the existence of a sanction. The Panel of Judges has a position in resolving the law on disputes between PT Bangun Karya Lestari and Nine Am Ltd. In this case an agreement between English-speaking countries must follow the rules stated in Article 31 paragraph (1) of the Language Law, which means that the Loan Agreement is obliged to speak Indonesian .